Analysis of Total Terpenoids from Maniltoa Grandiflora (A. Gray) Scheff Leaves Using TLC and HPLC Methods - Jhon Patar Sinurat; Visensius Krisdianilo; Reh Malem br Karo; Rinaldo Berutu (Stannum : Jurnal Sains dan Terapan Kimia, 2020)
Terpenoids screening were carried out using Liebermann Burchard and Salkowski reagent on the extract of Saputangan leaves. It showed that the leaves contained terpenoid compounds with appeared of a reddish brown ring in the extract and a reddish brown stain appeared on the TLC plate tested with 1% CeSO4 reagent in 10% H2SO4. The macerate of saputangan leaves processed separation using the partition method (Liquid-liquid Extraction). Extracts dissolved with methanol were partitioned with n-Hexane and then partitioned between aquadest and ethyl acetate in a ratio of 1: 1 to obtain 50 g of total terpenoids. Furthermore, TLC analysis was performed on total terpenoids using n-hexane: ethyl acetate (80:20 v/v) solvent to obtain 11 separate stains on the TLC plate with different Rf each. Analysis was enhanced in HPLC using 100% acetonitrile and 0.1% phosphoric acid at a wavelength of 210 nm, a flow rate of 0.500 mL/min and eluted for 30 minutes. Based on the HPLC results, there were 25 peaks which indicated the presence of total terpenoid compounds with the highest peak being peak no. 8 (ret.time's 6.234, area's 8503532 and height's 276032), peak no. 9 (ret.time's 6.674, area's 3322572 and height's 141859) and peak no. 10 (ret.time's 7.288, area's 2758231 and height's 103927)